Mechanical properties of biopolymers reinforced with carbon nanotubes - Blond, David (Trinity College (Dublin, Ireland). School of Physics, 2008)
Three biopolymers; poly(methyl methacrylate) (PMMA); poly(L-lactic acid) (PLLA); poly(vinyl alcohol) (PVA) and an engineered spider silk (Biosteel ®) have been independently doped with carbon nanotubes. PM MA was functionalised with OH-functionalised multiwalled carbon nanotubes (OH-MWNTs) by in situ polymerisation. Infrared absorbance studies revealed covalent bonding between the polymer strands and the nanotubes. The treated nanotubes were blended in solution with both in-house synthesised PMMA and commercial PMMA before drop-casting to form composite films. For composites blended with in-house synthesised PMMA, increases in the Young’s modulus (Y), breaking strength (δb), ultimate tensile strength (δc), and toughness (T) of x1.9, x4.7, x4.6, and x 13.7 respectively were observed upon the addition of less than 0.5 wt% nanotubes. For commercial PMMA, the increases in the above mentioned mechanical parameters were x 1.2, x 1.5, x 1.5, and x3 respectively. In both cases, effective reinforcement was only observed for nanotube contents of up to ~0.1 vol %. Above this volume fraction, all mechanical parameters tended to reduce, probably as a result of nanotube aggregation. In addition, scanning electron microscopy (SEM) studies of the composite fracture surfaces after film breakage showed that a polymer layer coated the nanotubes. The fact that the polymer rather than the interface fails suggests that functionalisation results in an extremely high polymer/nanotube interfacial shear strength.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin